2018
DOI: 10.1093/schbul/sby082
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: Biological Parameters of the Connection to Schizophrenia

Abstract: It is increasingly evident that the brain is not truly an immune privileged site and that cells of the central nervous system are sensitive to the inflammation generated when the brain is fighting off infection. Among the many microorganisms that have access to the brain, the apicomplexan protozoan Toxoplasma gondii has been one of the most studied. This parasite has been associated with many neuropsychiatric disorders including schizophrenia. This article provides a comprehensive review of the status of Toxop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 97 publications
1
97
0
1
Order By: Relevance
“…Their primary hosts are cats [22]. T. gondii affects the brain through inflammation or changes in the microbiome [45]. As several experiments have shown, T. gondii alters the behavior of rodents, making them easier prey for cats [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their primary hosts are cats [22]. T. gondii affects the brain through inflammation or changes in the microbiome [45]. As several experiments have shown, T. gondii alters the behavior of rodents, making them easier prey for cats [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mice infected by T. gondii once lose innate aversion for cat's urine permanently even after the infection has been removed [46]. In humans, T. gondii may be associated with an elevated risk for mental health issues, such as psychosis-like symptoms, bipolar disorder, violence, suicide attempts, anxiety disorder, and obsessive disorder [45]. In summary, a cat can be an infection source of T. gondii in its owner, causing brain dysfunction by inflammation or alteration in the microbiome, and leading to psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Synapse loss and neuroinflammation characterize many neurodegenerative diseases, including Alzheimer's disease, Parkinson's disease, and multiple sclerosis (3,4). Toxoplasma has been implicated in several neurodegenerative diseases (33), but the mechanisms underlying such associations are not known. We set out to test the effect of chronic Toxoplasma infection on neuronal degeneration in mice and to explore the potential mechanisms that are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Infection can be asymptomatic in humans but it can also cause significant disease in congenitally infected infants, immunodeficient patients and occasionally, in immunocompetent individuals. More recent studies have revealed an association with psychiatric disorders, such as schizophrenia and bipolar disorder [5,6] as well as neurologic disease, such as Alzheimer's [7]. T. gondii is also a veterinary problem, causing illness in domestic and wild animals [8].…”
Section: Widespread Distribution Of Toxoplasmosismentioning
confidence: 99%